Integration of Problem Based Learning at Kathmandu Medical College - Lama, Pratik Yonjan; Koirala, Pramesh; Bhattarai, Binita; Suwal, Gopal; Deshar, Sunkeshari (Journal of Kathmandu Medical College, 2014)
Problem based learning as an alternative method of teaching had its initiation in Nepal at the Institute of Medicine, Maharajgunj in 1978. From 2011, problem based learning has been introduced into the curriculum of all the medical colleges under Kathmandu University. However, successful implementation into the curriculum is still in the process of development. The objective of the article is to have a profound view on the students’ perspective towards the integration of Problem Based Learning in MBBS curriculum and the possible action plans for the effective implementation. A questionnaire survey was done in which a total of 114 out of 150 students of Kathmandu Medical College, MBBS second year participated. The results obtained suggested that problem based learning helps students remember and understand better than traditional lectures, increases integrative ability, self directed learning, sharpens analytic skills and develops group skills. Students believe that the role of facilitator in problem based learning in Kathmandu Medical College has been to motivate students, evaluate them and make a real effort in understanding their difficulties. However there are not enough sessions to cover the system blocks, aims and objectives in the course curriculum are not clear, topics covered in the sessions of problem based learning should be covered in the lecture hours also and meeting among the facilitators with an inclusion of a student representative has to be made. However, in the view of current scenario of student centered teaching, problem based learning has made a positive impact in students’ learning experience. DOI: http://dx.doi.org/10.3126/jkmc.v2i3.9969Journal of Kathmandu Medical College Vol. 2, No. 3, Issue 5, Jul.-Sep., 2013Page: 162-166Uploaded date : 3/4/2014